“Be exalted, o God, above the Heavens!” (Psalm 108:6) : studies in the book of Psalms and its reception presented to Phil J. Botha on his 65th birthday: editorial - Prinsloo, Gert T. M.; Weber, Beat (Old Testament Essays, 2019)
A new psalm had to be composed for new circumstances. It made use of a well-known oracle of God, but in a new political, social, religious, and/or historical context, that oracle had a new message. In a context of praise, it opened a perspective to the future. It emphasized in a new way that God had to bring about the new dispensation, and that he would. They gave the faithful a new historical and cosmological perspective.
free